Finding solace in the soil : an archaeology of gardens and gardeners at Amache - Clark, Bonnie J. (University Press of Colorado, 2020)
"Tells the largely unknown story of the gardens of Amache, the War Relocation Authority incarceration camp in Colorado. Combining physical evidence with oral histories, archival data, personal photographs, and memories of former Amache incarcerees, the book describes how gardeners cultivated community in confinement"